148k views
3 votes
g Use the properties of the natural logarithm to rewrite each logarithmic expression as an expression with a single logarithm. a . ln ( x + 5 ) − ln ( x − 5 ) = b . ln ( x + 5 ) + ln ( x − 5 )

1 Answer

4 votes

Answer:

Given:

(a.) ㏑( x + 5 ) − ㏑( x − 5 )

(b.) ㏑( x + 5 ) + ㏑( x − 5 )

To compute the above expression, we'll use the properties of natural logarithm. i.e.

㏑(a) − ㏑(b) = ㏑
(a)/(b)

∴ ㏑( x + 5 ) − ㏑( x − 5 ) = ㏑
(x+5)/(x-5)

Similarly

㏑(a) + ㏑(b) = ㏑
(a* b)

∴ ㏑( x + 5 ) + ㏑( x − 5 ) = ㏑(
x^(2)-25)

User Arcanefoam
by
5.9k points